DAMPAK PROGRAM REKLAMASI BAGI EKONOMI RUMAH TANGGA NELAYAN DI KOTA MANADO - Wagiu, Max (Sam Ratulangi University, 2011)
This study focused on the economic and the social impacts of the reclamation program for the traditional fishermen who live along the coastal area of Manado City set the reclamation program, particularly Wenang Selatan, Titiwungen, and Bahu-Malalayang, using direct observation and guided interview techniques to selected respondent. The results found that in economic aspect, the local people gained higher income before reclamation than after it; in social aspect, the former fishermen had to alter their profession to the one they did not know or were sent outside the city, even far from social facilities, such as school, health services, etc.